Dynamics of Islamic Economic Principles on Selected Components of the Millennium Development Goals towards Human and National Development - Imam Arikewuyo, Abdus-Sami'i (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The Millennium Development Goals (MDGs) constitutes the international development goals that were established following the Millennium Summit of the United Nations in 2000, upon the adoption of the United Nations Millennium Declaration. Essentially, the MDGs is aimed at creating a developed, peaceful and enabling environment to live in. The target period to accomplish the set goals is scheduled for 2015. What happens after 2015 is yet to be declared; though concerns are being raised presently in high-level thematic debates on Post- 2015 development process. It is striking that the declaration of the United Nations at the commencement of the twenty first century had always been the central nerve of Islam since its inception in the early seventh century; that is, over one thousand and three hundred years before the United Nations declaration on its MDGs. Islam as an encompassing religion does not only embrace peace in all ramifications, it evolves mechanism for an all-inclusive integration of its adherents and over all development of the ‘ummah (Muslim community). It, therefore, regulates both the spiritual and mundane affairs of its adherents; yet, without time bound. Thus, Islam is replete of injunctions that withstand the test of time on the principles and practice of all aspects of life including the religious, political, economic and social spheres with due recognition to gender requirements. It is laudable that the MDGs envision the well-being of man and his environment. However, it is mind-boggling that the duration envisaged by its proponents is almost expiring; yet, at the first quarter of its final year (i.e. 2015), the target is yet to be realized. A consideration of this failure prompts the need to study in this paper the dynamism of the Islamic economic principles in relation to the components of the MDGs with economic bias. Hence, the paper focuses on components 1 and 3 with a view to examine the efficacy of the provisions of Islam on the stipulated agenda vis-à-vis the United Nations Millennium Declaration towards fostering national development. Both descriptive and analytical approaches were employed in carrying out the study.